Gamma-Fe2O3-MoO3 molecular oxygen catalyst capable of being magnetically recycled to directly generate < 1 > O2 as well as preparation method and application of gamma-Fe2O3-MoO3 molecular oxygen catalyst

The γ-Fe2O3@MoO3 molecular oxygen catalyst directly converts O2 to 1O2, solving the problem of low phosphate recovery efficiency in sludge, achieving efficient wall-breaking phosphorus release and magnetic recovery of catalysts, and has the potential for industrial application.

CN119500168APending Publication Date: 2025-02-25CHONGQING UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411617944.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recover phosphate from sludge, and homogeneous catalysts cannot be recovered, limiting its industrial application.

Method used

The γ-Fe2O3@MoO3 molecular oxygen catalyst is used. This catalyst is prepared by a simple impregnation method and is magnetically capable. It can directly convert O2 to 1O2 without intermediate state changes. It is suitable for the wall-breaking phosphorus release process of sludge and can be recovered through magnetic properties.

Benefits of technology

It achieves efficient wall-breaking and phosphorus release within a wide pH range, consumes less chemical energy, and the catalyst can be reused, reducing transportation and storage costs, and has the potential for industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500168A_ABST
    Figure CN119500168A_ABST
Patent Text Reader

Abstract

The invention discloses a gamma-Fe2O3-MoO3 molecular oxygen catalyst capable of being magnetically recycled and directly generating < 1 > O2 as well as a preparation method and application of the gamma-Fe2O3-MoO3 molecular oxygen catalyst, and the gamma-Fe2O3-MoO3 molecular oxygen catalyst is prepared according to the following steps: (1) preparing gamma-Fe2O3, (2) putting ammonium molybdate hexahydrate into a muffle furnace to react at 500-550 DEG C, and then cooling to obtain MoO3; (3) sufficiently mixing MoO3 and gamma-Fe2O3, uniformly grinding, adding water, and mechanically stirring; and then putting the mixture into a drying oven to be dried, so as to obtain the reddish brown catalyst gamma-Fe2O3-coated MoO3. The preparation of the heterogeneous molecular oxygen catalyst can be completed by adopting a simple impregnation method. Molecular oxygen can be activated within the pH range of 3-10, intermediate state change is not needed, and the step of directly converting O2 into < 1 > O2 is followed, so that the wall-breaking phosphorus release process of sludge is realized. And the catalyst can be recovered through magnetism. The method is different from previous reports, and the potential of the method in industrial application is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sewage sludge treatment materials, and specifically to a magnetically recyclable material directly generated from O2 1 γ-Fe2O3@MoO3 molecular oxygen catalyst for O2, preparation method and application thereof. Background Art

[0002] Phosphate is a valuable crop nutrient and an indispensable substance in the synthesis of plant genetic material and protein. Currently, about 82% of mined phosphorus is used in agriculture, while 7% is used to produce animal feed. The remaining 11% of mined phosphorus is used in industry and medicine for the production of medicines, oils, detergents, and even textiles, so phosphorus is closely related to human life. The main commercial source of phosphate used in fertilizers is phosphate rock, but the mining rate exceeds the rate of natural regeneration, so it can be regarded as a non-renewable resource. In addition, according to the International Water Management Institute, by 2050, phosphorus production will increase by 70% overall, and even up to 100% in developing countries to meet the rapidly growing demand for phosphorus. However, almost 74% of the world's phosphate mines are in Morocco, and the distribution of the rest of the phosphorus is also uneven, so new technologies need to be developed to sustainably recover phosphate from other organic waste sources (such as sewage sludge) to maintain phosphorus security.

[0003] The activated sludge process is the most widely used technology for removing organic pollutants and nutrients in urban sewage treatment plants, which will produce a large amount of waste activated sludge (WAS) and more than 90% of phosphorus will be transferred to the excess sludge. Therefore, waste activated sludge can be regarded as a potential resource of phosphorus. An effective way to recover phosphorus from excess sludge is to precipitate magnesium ammonium phosphate (MAP) by adding an economically cost-effective magnesium source to form struvite. The product obtained by struvite crystallization can be used as an agriculturally effective slow-release fertilizer. Therefore, the use of struvite as a fertilizer can not only recycle but also reuse nutrients, thereby improving the sustainable management of sewage treatment plants. Although a lot of research has been done on the recovery of phosphorus from excess sludge using struvite crystallization, methods for effectively releasing phosphorus from excess sludge still need further research. So far, many processes for breaking phosphorus release from excess sludge have been developed. Sludge pretreatment methods can be divided into physical treatment, chemical treatment and biological treatment according to their technical characteristics. Among them, physical treatment generally involves high temperature, and biological treatment cycle is long. Although heterogeneous catalytic technology in chemical treatment can avoid the loss of metal ions in traditional technology, it cannot be reused and is easy to cause secondary metal pollution. However, the consumption of oxidants cannot be ignored, and expensive transportation costs will be generated during the transportation process. Similarly, ozone technology does not require the transportation of oxidants, but its high power consumption cannot be ignored.

[0004] As a green, non-toxic and inexpensive oxidant, molecular oxygen shows many advantages over other oxidants in sustainable and environmentally friendly degradation of pollutants. Molecular oxygen activation is a pioneering method in advanced oxidation processes that supports efficient environmental remediation by generating highly oxidative reactive oxygen species (ROS) with very little impact on the environment. In addition, molecular oxygen does not require specific high-energy-consuming equipment, reducing the cost of equipment procurement and oxidant transportation and storage. Currently, photocatalytic excited state photogenerated electrons are commonly used to activate molecular oxygen, breaking the spin-forbidden potential barrier present in molecular oxygen and converting it into ROS. In addition to photocatalysis, some new technologies, such as electrocatalysis, piezoelectric catalysis and photothermal catalysis, have also been shown to activate O2. The activation of molecular oxygen generally follows the following process:

[0005] O2+e-→O2· -

[0006] O2 - +2H+e +- →H2O2

[0007] O2+2e - →O2 2-

[0008] O2 2- +2H→H2O2

[0009] Singlet oxygen produced by O2 ( 1 O2) is an excited molecular oxygen with high energy and electrophilic properties. It is widely present in nature, and its important role is gradually extending from chemical synthesis and medical technology to environmental remediation. Electron-rich substances, such as unsaturated organic pollutants, sulfides, and microbial pathogens, are easily 1 O2 attack. The ability to cause severe irreversible damage to a variety of bacteria, viruses and fungi makes 1 O2 becomes an excellent ROS for antibacterial effects. 1 The oxidative and electrophilic properties of O2 have led to its application in pathogen inactivation, photodynamic cancer therapy (PDT), and organic synthesis for more than 80 years. In particular, it has gradually attracted widespread attention in environmental remediation in recent years.

[0010] Molecular oxygen activation 1 There are few reports on the research of O2. The only recent report shows that Zheng et al. used Cu 2+ and molybdenum powder, O2 is first converted to O2 - Convert to 1 O2. Zheng et al. used Fe 2+ And CoS2, O2 also follows the conversion to O2 first. - Convert to 1 O2 steps. In these two reports, O2- and 1 The EPR peak intensities of O2 are almost the same, which indicates that O2 is first converted into O2·- and then into 1 O2 mechanism. However, from the perspective of free energy, each additional reaction step consumes more chemical energy, which is not conducive to the reaction. Moreover, both types of catalysts are homogeneous systems and cannot be recycled, which limits their industrial application. Summary of the invention

[0011] In order to solve the above technical problems, the first object of the present invention is to provide a magnetically recyclable direct generation 1 The second purpose is to provide a method for preparing a γ-Fe2O3@MoO3 molecular oxygen catalyst that can be magnetically recovered and directly generated 1 The third purpose is to provide an application of the γ-Fe2O3@MoO3 molecular oxygen catalyst prepared by the present invention. The preparation of the heterogeneous molecular oxygen catalyst can be completed by a simple impregnation method. Molecular oxygen can be activated in the pH range of 3 to 9 without intermediate state changes, and O2 is directly converted to 1 The O2 step achieves the phosphorus release process of the sludge by breaking the wall. And the catalyst can be recovered by magnetism. This is different from previous reports and shows its potential for industrial application.

[0012] To achieve the first objective, the present invention is implemented by the following technical solutions: a magnetically recyclable direct generation 1 The method for preparing a γ-Fe2O3@MoO3 molecular oxygen catalyst of O2 is characterized in that the catalyst is prepared according to the following steps:

[0013] (1) preparing γ-Fe2O3, dissolving ferrous sulfate and PVP in deionized water, adding sodium hydroxide to adjust the pH to 9-10 under stirring, and then reacting at 85-90°C to form Fe3O4 nanoparticles, cooling to room temperature, removing the supernatant, collecting the precipitate by centrifugation, washing with deionized water and ethanol alternately, drying, and then placing the Fe3O4 nanoparticles in a muffle furnace, heating to 450-500°C for calcination, and cooling to room temperature after calcination to obtain γ-Fe2O3;

[0014] (2) placing ammonium molybdate hexahydrate in a muffle furnace and maintaining the temperature at 500-550° C. for reaction, and then cooling to obtain MoO3;

[0015] (3) After MoO3 and γ-Fe2O3 are fully mixed, they are evenly ground, water is added, and mechanical stirring is performed; and then they are placed in an oven for drying to obtain a reddish-brown catalyst γ-Fe2O3@MoO3.

[0016] In the above scheme: in step (1), during calcination, the heating rate is 8-10°C / min and the holding time is 3-4h.

[0017] In the above scheme: in step (2), the heating rate of the muffle furnace is 8-10°C / min, and the holding time is 40-50min.

[0018] In the above scheme: the mass ratio of γ-Fe2O3 to MoO3 is 1-7:3-9.

[0019] A magnetically recyclable direct generation 1 The γ-Fe2O3@MoO3 molecular oxygen catalyst prepared by the preparation method of γ-Fe2O3@MoO3 molecular oxygen catalyst of O2.

[0020] An application of the γ-Fe2O3@MoO3 molecular oxygen catalyst in the degradation of organic pollutants.

[0021] An application of the γ-Fe2O3@MoO3 molecular oxygen catalyst in sludge wall breaking to release phosphorus and recover phosphorus.

[0022] In the above scheme: adding acid or alkali to the concentrated sludge to adjust the pH to 3-9, adding a catalyst, stirring evenly, introducing air, and after the reaction is completed, first using a magnet to recover the catalyst in the broken sludge, then centrifuging to separate the clear liquid, filtering the clear liquid, and then adding sodium hydroxide to the clear liquid to adjust the pH to 9-10, adding magnesium chloride to stir the reaction, and then centrifuging to obtain a precipitate, and drying the precipitate to obtain struvite.

[0023] The present invention proposes to prepare molecular oxygen catalyst by using γ-Fe2O3 and MoO3 through a simple impregnation method, so as to achieve phosphorus release from sludge by breaking the wall, and to recover the released phosphorus by using the struvite method, which has the following advantages:

[0024] (1) When O2 is converted to 1 In O2, the catalyst is a magnetic heterogeneous catalyst that can be recycled and reused through magnetic recovery, which is significantly different from the previous O2 conversion 1 Homogeneous catalyst for O2.

[0025] (2) The catalyst of the present invention can directly convert O2 into 1 O2, there is no O2·- intermediate conversion process, this step reaction will consume less chemical energy, require less catalyst, and have higher reaction efficiency.

[0026] (3) Under the condition of pH 3-9, it has the effect of breaking the cell wall and releasing phosphorus in sludge. The applicable pH range is wide, and the effect of breaking the cell wall and releasing phosphorus in sludge is good. It can recover phosphorus in sludge cells very well. It can also degrade organic pollutants such as rhodamine.

[0027] (4) In the process of degrading organic pollutants and recovering phosphorus by breaking the sludge wall to release phosphorus, the molecular oxygen catalyst application process does not require high-energy-consuming equipment such as ozone generators, nor does it require the transportation and storage costs and storage space of traditional oxidants such as hydrogen peroxide and persulfate. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Figure 3 shows the degradation of rhodamine by different proportions of γ-Fe2O3 and MoO3, where (a) is the degradation effect diagram of rhodamine B by different mass proportions of γ-Fe2O3 and MoO3; (b) is the first-order kinetic equation for the degradation of rhodamine B by different mass proportions of γ-Fe2O3 and MoO3; (c) is the effect diagram of the degradation of rhodamine B by γ-Fe2O3 and MoO3 alone.

[0029] Figure 2 (a) is the XRD spectra of γ-Fe2O3, MoO3 and γ-Fe2O3@MoO3, (b) and (c) are schematic diagrams of the magnetism of γ-Fe2O3@MoO3.

[0030] Figure 3 (a)-(c) are the heterojunction structures of γ-Fe2O3@MoO3 and their appearances, and (d)-(f) are the element distribution diagrams of the catalysts.

[0031] Figure 4 This is a diagram showing the effect of sludge wall breaking and phosphorus release under different conditions.

[0032] Figure 5 The changes of liquid phase phosphorus / total phosphorus (%) and supernatant COD (mg / L) during the cell wall breaking process under different pH conditions.

[0033] Figure 6 (a)-(b) show the changes in liquid phase phosphorus / total phosphorus and supernatant COD (pH=3) during the cell wall breaking process; (c)-(d) are microscope images of original sludge, and (e)-(f) are microscope images of sludge after cell wall breaking.

[0034] Figure 7 (a) is the appearance and three-dimensional fluorescence spectrum of the extracellular polymers of the original sludge, (b) is the appearance and three-dimensional fluorescence spectrum of the extracellular polymers of the sludge after cell wall breaking, (c) is the three-dimensional fluorescence distribution percentage of different types of extracellular polymers of the sludge before and after cell wall breaking, and (d) is the change of extracellular polymers of the sludge during the cell wall breaking process.

[0035] Figure 8 (a), (b), and (c) are ·OH, O2·-, and 1 The EPR spectra of O2 and the quencher effect diagram, (d) are (tert-butyl alcohol (TBA, quencher of ·OH), p-benzoquinone (p-BQ, quencher of O2·-), L-tryptophan (TP, 1O2 quencher) and catalase (CAT, H2O2 quencher), None (blank control group)).

[0036] Fig. 9 This is a diagram showing the effect of catalyst reuse.

[0037] Fig.10 (a) shows the appearance of the recovered, ground and dried struvite, and (b) shows the XRD spectrum of the struvite. DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0039] Example 1

[0040] Under continuous mechanical stirring, 0.83g FeSO4·7H2O and 1.0g PVP were placed in 100mL deionized water. After stirring evenly, NaOH solution was added to adjust the pH to 9-10. Then, under the continuous stirring of the mechanical stirrer, the solution was fully reacted at 85-90℃ for 3 hours to form Fe3O4 nanoparticles. Then, after cooling to room temperature, the upper liquid was poured off, the precipitate was collected by centrifugation, washed alternately with deionized water and alcohol for 5 times, and then dried in a blast oven at 80℃. Finally, the obtained Fe3O4 was placed in a ceramic crucible with a lid. The crucible was then placed in a muffle furnace with a heating rate of 8-10℃ / min and heated to 450-500℃ for 3-4 hours. After cooling to room temperature, the desired γ-Fe2O3 was obtained.

[0041] Place ammonium molybdate hexahydrate into a muffle furnace, heat at a rate of 8-10°C / min, maintain the temperature at 500-550°C for 40-50 minutes, and then cool to obtain MoO3.

[0042] The mass ratios of γ-Fe2O3 and MoO3 were 1:9, 2:8, 3:7, 4:5, 5:5, 6:8, and 7:3, respectively, and then the mixture was fully mixed and evenly ground for 5 minutes, 50 ml of water was added, and mechanical stirring was performed for 1 hour. The mixture was placed in an oven at 80°C and dried for 12 hours to obtain a reddish-brown catalyst γ-Fe2O3@MoO3.

[0043] Figure 1 The degradation effect of rhodamine B with different mass ratios of γ-Fe2O3 and MoO3 was demonstrated.

[0044] 100ml of 10mg / L Rhodamine B, add 0.2g of catalyst, air volume 2L / min, mechanical stirring 400r / min,

[0045] from Figure 1It can be seen from (a) that after 10 min of degradation, the γ-Fe2O3 and MoO3 catalysts with different mass ratios almost completely degraded Rhodamine B. Figure 1 (b) shows that the catalyst with γ-Fe2O3:MoO3=3:7 has the largest first-order kinetic reaction constant, so γ-Fe2O3:MoO3=3:7 (mass ratio) is selected as the optimal ratio. Figure 1 .(c) shows that γ-Fe2O3 and MoO3 alone have no molecular oxygen oxidation effect.

[0046] Figure 2 .(a) Confirm the composition of the catalyst prepared by the present invention. Figure 2 .(b) and (c) show that the catalyst is magnetic and can be recovered magnetically.

[0047] Figure 3 .(a)-(c) show that γ-Fe2O3@MoO3 is a heterojunction structure and its appearance. Figure 3 .(d)-(f) show the element distribution of the catalyst. It is worth noting that γ-Fe2O3 is not obvious in the XRD spectrum of γ-Fe2O3@MoO3. The reason is that the particle size of γ-Fe2O3 is much smaller than that of MoO3, and its crystal surface is easily obscured by MoO3. However, the SEM / mapping image of γ-Fe2O3@MoO3 can intuitively reflect the element distribution and structure of γ-Fe2O3 and MoO3 in the catalyst.

[0048] Example 2

[0049] Treatment of Phosphorus Release from Sludge

[0050] Add sulfuric acid solution or alkali solution (50% sulfuric acid) to 100ml of raw sludge, adjust the pH to 3, 4, 5, 6, 7, 8, 9 respectively, and then add 0.7g of the above-synthesized γ-Fe2O3@MoO3 (γ-Fe2O3: MoO3 mass = 3:7) respectively, stir evenly mechanically, and then directly introduce 4L / min of air for molecular oxygen oxidation reaction. Sample 5mL of sludge every 10min to detect the reaction results. The sampled sludge is centrifuged at 4000r / min for 5min to obtain the supernatant, and then filtered with a 0.45μm water filter membrane, and the COD (used to characterize the wall breaking effect) and phosphorus content (used to characterize the phosphorus release effect) of the filtrate are determined with a water quality detector. The total phosphorus of the raw sludge is set as total phosphorus, the supernatant is set as liquid phosphorus, and the phosphorus recovery rate = liquid phosphorus / total phosphorus*100%. After the reaction is completed, the catalyst in the broken sludge is first recovered with a magnet, and then the clear liquid is centrifuged and filtered with a sand core funnel with a 0.45μm filter membrane. 6ml of sodium hydroxide solution (1mol / L) is added to the filtered clear liquid to adjust the pH to 9, and then magnesium chloride solid with a molar ratio of Mg: liquid phosphorus of 1.4:1 is added. After stirring for 3 hours, centrifuge at 4000r / min for 10min to obtain the lower part of the struvite precipitate, and finally put it into a 40℃ oven for drying to obtain the finished struvite.

[0051] Figure 4 The effect of oxidation wall breaking to release phosphorus under different oxidation conditions is shown. It can be seen from the figure that effective oxidation wall breaking to release phosphorus will only occur when γ-Fe2O3@MoO3 catalyst and oxygen are added. This shows that γ-Fe2O3@MoO3 is a necessary catalyst for activating molecular oxygen.

[0052] Figure 5 The effect of oxidative cell breaking and phosphorus release under different pH conditions is shown. The orange bar graph (high) in the figure represents the effect of oxidative cell breaking and phosphorus release under different pH conditions. The green part (short) is the sludge after pH adjustment, without adding catalyst, directly exposed to air and stirred for the same time. Figure 5 It can be seen from the figure that, without adding a catalyst, under acidic and alkaline conditions, the sludge itself can also break the cell wall and release phosphorus. However, its efficiency is obviously worse than adding a catalyst. It can be seen from the figure that under different pH conditions, the catalyst of the present invention can promote the sludge to break the cell wall and release phosphorus. The phosphorus removal rate is high. The catalyst can be used in a wide pH range and has strong adaptability.

[0053] Figure 6 (a)-(b) show the changes in liquid phase phosphorus / total phosphorus and supernatant COD during the cell wall breaking process. The phosphorus release rate reaches a maximum of 98% at 50 min. 1Due to the oxidation of O2, the organic matter in the sludge cells is released into the liquid phase in the initial stage, causing the COD to increase. Later, since the release of organic matter in the sludge cells is completed but the oxidation continues, the organic matter released in the liquid phase is mineralized, thereby reducing the COD in the liquid phase.

[0054] Figure 7 (a) Appearance and three-dimensional fluorescence spectrum of extracellular polymers of original sludge, (b) Appearance and three-dimensional fluorescence spectrum of extracellular polymers of sludge after cell wall breaking, (c) Three-dimensional fluorescence distribution percentage of different types of extracellular polymers of sludge before and after cell wall breaking, (d) Changes of extracellular polymers of sludge during cell wall breaking.

[0055] S-EPS represents free extracellular polymers, LB-EPS represents loose extracellular polymers, and TB-EPS represents tightly bound extracellular polymers. Figure 7 (a) and (b) show that the color of the extracellular polymers becomes darker after being oxidized by molecular oxygen, which indicates that due to the cell wall breaking effect, a large amount of organic matter is released into the liquid phase. The three-dimensional fluorescence spectra of three different extracellular polymers show that the composition (the five areas in each figure represent the different components of each extracellular polymer, and the color depth indicates the concentration) has changed. Figure 7 .(c) shows the specific values ​​of the changes in extracellular polymers before and after cell wall breaking. The five colors represent the area proportions of the five regions in the fluorescence image. Figure 7 .(d) shows the changes in the concentration of extracellular polymers during molecular oxygen oxidation.

[0056] Figure 8 Shows the results of the quenching experiment:

[0057] The quenching experiment was the same as the experiment on phosphorus release from sludge in Example 2, except that before adding the catalyst, a quenching agent was added, such as 0.5 ml of tert-butyl alcohol (TBA, quencher of ·OH), 200 mg of p-benzoquinone (p-BQ, quencher of O2·-), 200 mg of L-tryptophan (TP, 1 O2 quencher), 200 mg catalase (CAT, H2O2 quencher).

[0058] In the three EPR spectra, 1 The intensity of O2 is much greater than that of OH and O2 ●- The intensity, especially in the fifth minute, O2 - There is no relative strength. 1 The intensity of O2 reaches the maximum. This shows that in this catalytic reaction 1 O2 concentration and OH and O2 ●- In previous reports, due to the experience of O2→O2 ●- → 1O2 reaction process, so O2 ●- and 1 The relative intensity of the EPR spectrum of O2 remains almost consistent.

[0059] Meanwhile, in the quencher experiment, only TP produced a quenching effect. 1 O2 occupies an absolute dominant position, and ·OH and O2·- are only slight side reactions. Therefore, the contribution of ·OH and O2·- to sludge wall breaking is so small that there is no corresponding quenching effect.

[0060] The recovered catalyst is reused, and the effect is shown in the figure Fig. 9 As shown, from Fig. 9 It can be seen that repeated use does not affect the catalytic effect of the catalyst of the present invention. Fig.10 This is the appearance and XRD diagram of the struvite recovered by this catalytic system.

[0061] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A magnetically recyclable direct generation 1 The method for preparing a γ-Fe2O3@MoO3 molecular oxygen catalyst of O2 is characterized in that: Prepare according to the following steps: (1) preparing γ-Fe2O3, dissolving ferrous sulfate and PVP in deionized water, adding sodium hydroxide to adjust the pH to 9-10 under stirring, and then reacting at 85-90°C to form Fe3O4 nanoparticles, cooling to room temperature, removing the supernatant, collecting the precipitate by centrifugation, washing with deionized water and ethanol alternately, drying, and then placing the Fe3O4 nanoparticles in a muffle furnace, heating to 450-500°C for calcination, and cooling to room temperature after calcination to obtain γ-Fe2O3; (2) placing ammonium molybdate hexahydrate in a muffle furnace and maintaining the temperature at 500-550° C. for reaction, and then cooling to obtain MoO3; (3) After MoO3 and γ-Fe2O3 are fully mixed, they are evenly ground, water is added, and mechanical stirring is performed; and then they are placed in an oven for drying to obtain a reddish-brown catalyst γ-Fe2O3@MoO3.

2. According to claim 1, the magnetically recoverable direct generation 1 The preparation method of γ-Fe2O3@MoO3 molecular oxygen catalyst of O2 is characterized by: In step (1), during calcination, the heating rate is 8-10°C / min and the holding time is 3-4h.

3. According to claim 2, magnetically recoverable direct generation 1 The preparation method of γ-Fe2O3@MoO3 molecular oxygen catalyst of O2 is characterized by: In step (2), the heating rate of the muffle furnace is 8-10°C / min, and the holding time is 40-50min.

4. The magnetically recyclable direct generation according to any one of claims 1 to 3 1 The preparation method of γ-Fe2O3@MoO3 molecular oxygen catalyst of O2 is characterized by: The mass ratio of γ-Fe2O3 to MoO3 is 1-7:3-9.

5. A magnetically recoverable direct generation method as claimed in any one of claims 1 to 4 1 The γ-Fe2O3@MoO3 molecular oxygen catalyst prepared by the preparation method of γ-Fe2O3@MoO3 molecular oxygen catalyst of O2.

6. Use of the γ-Fe2O3@MoO3 molecular oxygen catalyst according to claim 5 in the degradation of organic pollutants.

7. Use of the γ-Fe2O3@MoO3 molecular oxygen catalyst as claimed in claim 5 in phosphorus recovery by sludge wall breaking and phosphorus release.

8. The use according to claim 7, characterized in that: Add acid or alkali to the concentrated sludge to adjust the pH to 3-9, add a catalyst, stir evenly, and introduce air. After the reaction is completed, first use a magnet to recover the catalyst in the broken sludge, then centrifuge to separate the clear liquid, filter the clear liquid, then add sodium hydroxide to the clear liquid to adjust the pH to 9-10, add magnesium chloride to stir the reaction, then centrifuge and dry to obtain struvite.